Uric Acid: A Potential Marker For Predicting Maternal And Fetal Morbidity - Javed, Aeman; Tahir, Umber Arooj; Tauseef, Hafsa; Hussain, Syeda Luba; Siddiqui, Sana Shaukat (Journal of Rawalpindi Medical College, 2024)
Objective: To find out serum uric acid levels in normal and preeclamptic pregnant women in the third trimester. Methods: It was a cross-sectional analytical study conducted from July 2022 to December 2023. All primigravida women aged 20-45 years in the third trimester of singleton pregnancy attending in Obstetrics and Gynecology outpatient department of Ibn-e-Seina Hospital in study duration were included in the study. After obtaining approval from the ethical review committee and informed consent from the participants, relevant data were recorded on a predefined data sheet. Statistical analysis was performed by using SPSS version 14. A chi-square test was performed to find the statistical difference regarding uric acid distribution between groups and the ‘p’ value <0.05 was considered as significant. Results: A total of 1264 subjects were included in the study fulfilling the inclusion and exclusion criteria. The mean age of the study participants was 28.5±08.43 years with a mean gestational age of 29.35±3.08 weeks. Out of a total of 1264 women, 85.1% were normal and 14.9% had preeclampsia. In our study out of 189 preeclamptic women, 54.5% had raised serum uric acid levels. The difference between uric acid levels between preeclamptic and non-preeclamptic women was found to be significant (p<0.001). Conclusion: Serum uric acid level in pregnant women can be used as a useful and inexpensive marker in the prediction of preeclampsia and preventive measures can be taken accordingly.